2000
DOI: 10.1002/1520-7560(200005/06)16:3<172::aid-dmrr117>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Blunted erythropoietin response to anemia in patients with Type 1 diabetes

Abstract: The majority of patients with Type 1 diabetes who had anemia also had low EPO levels. The pathogenesis of this phenomenon is probably multifactorial. Autonomic neuropathy appears to play a role, but it is not sufficient, per se, to be the only cause. Dysautonomia might enhance the effect of renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Anaemia in diabetes may be associated with blunted erythropoietin response 32 33. Erythropoietin has been shown to have neuroprotective effects in animal models,34 35 offering another possible explanation for the association between DPN and anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia in diabetes may be associated with blunted erythropoietin response 32 33. Erythropoietin has been shown to have neuroprotective effects in animal models,34 35 offering another possible explanation for the association between DPN and anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that anemia occurs earlier in the course of diabetic nephropathy than in other forms of kidney disease, and anemia has been described among patients with mild to moderate chronic kidney disease (e.g., GFR 30–59 ml/min/1.73 m 2 ) as well as among those with more severe kidney disease [4]. Hypotheses to explain a higher rate of anemia among people with diabetes include damage to renal architecture produced by chronic hyperglycemia and consequent formation of advanced glycation end products [5]; autonomic neuropathy with decreased splanchnic sympathetic stimulation of erythropoietin production [6]; a blunted erythropoietin response to anemia among erythropoietin-producing cells [7]; and systemic inflammation [8]. Prior population-based studies in the United States have shown that chronic kidney disease-associated anemia is more prevalent among blacks than whites [9].…”
Section: Introductionmentioning
confidence: 99%
“…Serum EPO levels were decreased in type 1 diabetic patients with postural hypotension in comparison to age- and duration-matched type 1 diabetics free of complications as well as non-anemic, non-diabetic controls and patients with iron deficiency anemia (Winkler et al, 1999). A blunted EPO response to severe anemia has also been described as a result of autonomic neuropathy in studies of patients with both types 1 and 2 diabetes (Ricerca et al, 1999; Cotroneo et al, 2000; Spallone et al, 2004; Saito et al, 2007). …”
Section: Discussionmentioning
confidence: 91%